2007
DOI: 10.1159/000108135
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Soybean Protein β-Conglycinin α′-Subunit Expression and Induced Hypersensitivity Reaction in Rats

Abstract: Background: The major storage protein in soybean seed is β-conglycinin and this protein has been identified as being responsible for food-allergic reactions in several species. However, the mechanism through which β-conglycinin induces an allergic reaction has not yet been elucidated. In addition, assessing the antigenic activity of β-conglycinin by studying the activity of a subunit has rarely been conducted. Therefore, the objective of the present study was to characterize the antigenic specificity of the β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 70 publications
0
18
0
4
Order By: Relevance
“…Moreover, it is incredibly time consuming and depends on expensive equipment. In comparison, prokaryotic recombinant protein expression systems (E. coli) have several advantages, including ease of culture, rapid cell growth, and relatively simple purification procedures (Bohle and Vieths 2004;Clavijo et al 2004;Guo et al 2008;Lorenz et al 2001;Utsumi et al 2002). In addition, immunoblot analysis showed that both soybean and recombinant P34 proteins cross-reacted not only with polyclonal and monoclonal antibodies produced against P34 and crude soybean protein but also with the sera from 361 patients with atopic dermatitis; it means that the recombinant P34 is immunologically reactive, indicating that the recombinant P34 expressed by E. coli has similar epitope structures to natural soybean P34 protein and thus can be used as the standard allergen of P34 (Babiker et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is incredibly time consuming and depends on expensive equipment. In comparison, prokaryotic recombinant protein expression systems (E. coli) have several advantages, including ease of culture, rapid cell growth, and relatively simple purification procedures (Bohle and Vieths 2004;Clavijo et al 2004;Guo et al 2008;Lorenz et al 2001;Utsumi et al 2002). In addition, immunoblot analysis showed that both soybean and recombinant P34 proteins cross-reacted not only with polyclonal and monoclonal antibodies produced against P34 and crude soybean protein but also with the sera from 361 patients with atopic dermatitis; it means that the recombinant P34 is immunologically reactive, indicating that the recombinant P34 expressed by E. coli has similar epitope structures to natural soybean P34 protein and thus can be used as the standard allergen of P34 (Babiker et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, bioelimination of histamine has attracted considerable interest because inadequate bioavailability of histamine has been linked to a number of pathological conditions [2,[8][9][10][11]. The current understanding of histamine bioelimination distinguishes between local and systemic components.…”
Section: Discussionmentioning
confidence: 99%
“…In pathological conditions like allergy, asthma, parasitic disease or mastocytosis, very high amounts of histamine can be released from mast cells and basophils [2,[8][9][10][11]. When the capacity for local histamine elimination is overtaxed, the amine spills over into the systemic circulation and can give rise to deleterious elevations in plasma histamine level [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Protein content was determined by the Kjeldahl method and purity was analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) using mini-gel apparatus (BioRad Laboratories, CA, America) followed by Coomassie Brilliant Blue R-250 staining. The gel was scanned by Bio Imaging System with Gene Genius (Syngene, USA), and the purity of glycinin was measured by GeneTools Analysis Software, Version 3.03.03 (Guo et al, 2008). Glycinin and β-conglycinin were glycated with FOS according to the Maillard reaction in powder system described by Jürgen et al (2007).…”
Section: Isolation Of Glycinin and β-Conglycinin And Glycated With Fosmentioning
confidence: 99%
“…Soybean is considered to be one of the major food allergens, which is more prominent in the industrial countries (Wang, Qin, Sun, & Zhao, 2014). In recent years, soybean allergy has become a public problem all over the world (Guo, Piao, Cao, & Ou, 2008;Wang et al, 2014). Glycinin and β-conglycinin are two major antigen proteins in soybean and they accounted for about 65-80% of the total seed protein.…”
Section: Introductionmentioning
confidence: 99%